Effects of Education on the Use of Personal Protective Equipment for Reduction of Contamination: A Randomized Trial. (July 2020) - Yeon, Jeong Hwa; Shin, Yong Soon
Introduction: Accurate doffing personal protective equipment (PPE) is one of the key practices of infection control because of increased risk of infection transmission caused by medical garments or environmental contamination. Objectives: The study aimed to develop a reality-based education program and identify its effects on nurses' knowledge, attitudes, and contamination after PPE doffing. Methods: Randomized control group pretest–posttest design. A total of 56 nurses were randomly assigned to experimental ( n  = 28) and control ( n  = 28) groups. The experimental group underwent a new reality-based education program to improve PPE use. Subsequently, participants were assessed on knowledge of and attitude toward PPE use, as well as number and area of contaminated sites after removing PPE and mask fitting test. Results: There were no significant differences in knowledge and attitude to PPE use. The experimental group had significantly fewer contaminated sites than the control group (42 vs. 89), and a significantly lower mean contaminated site area (16.63 ± 24.27 vs. 95.41 ± 117.51 cm 2 ). The tuberculosis mask fitting test success rates were 68% and 50% in the experimental and control groups, respectively, but the difference was not significant. Conclusion: The reality-based education on use of PPE helps to reduce contamination and improve performance related to the use of PPE for infection control.